Selective deficits in prefrontal cortical GABAergic neurons in schizophrenia defined by the presence of calcium-binding proteins - Beasley, Clare L; Zhang, Zhi J; Patten, Iain; Reynolds, Gavin P (Biological psychiatry (1969), 2002)
Background: Postmortem studies have provided evidence for abnormalities of the γ-aminobutyric acid (GABA)-ergic system in schizophrenia, including deficits of GABA-containing interneurons. The calcium-binding proteins parvalbumin, calbindin, and calretinin can be used as markers for specific subpopulations of cortical GABAergic interneurons. Methods: Following our previous observation of a reduction in the density of parvalbumin- but not calretinin-immunoreactive cells in the prefrontal cortex (Brodmann area 10) in schizophrenia, we have quantified the laminar density of neurons immunoreactive for the calcium-binding proteins parvalbumin, calbindin, and calretinin in a further prefrontal cortical region (Brodmann area 9) in patients with schizophrenia, bipolar disorder, major depression, and in matched control subjects (each group n = 15). Results: Initial statistical analysis revealed reductions in the total cortical density of parvalbumin- and calbindin- but not calretinin-immunoreactive neurons in schizophrenia relative to control subjects. Further analysis comparing individual laminar densities between groups indicated that, following correction for multiple comparisons, only a reduction in calbindin-immunoreactive neurons in cortical layer II in the schizophrenic group attained statistical significance. Conclusions: These findings suggest that deficits of specific GABAergic neurons, defined by the presence of calcium-binding proteins, are present in schizophrenia. Trends toward similar reductions are observed in bipolar disorder.